Skepticism and truth: essay on the radical universality of a post-skeptical thought - Andrade, Abrahão Costa (Faculdade de Filosofia e Ciências, 2018)
Based on a study of the tropes of Aenesidemus discussed by Sextus Empiricus in hisPyrrhoniae Hypotyposes, we propose a reading which leads us to the need to postulate for contemporarythought a new universality that is radical and insurmountable. By this means, the philosophicalcontent and scope of skepticism can be understood in the sense of an encounter – finally – with themuch sought after notion of truth as that which can not be possessed, or whose announced possessionis always the revelation of a one-sidedness. In addition, a place of non-relativistic thought can besecured against dogmatic intolerance and against dissatisfaction with the conflicts of philosophy.